Comparison of methods for genomic DNA isolation of rhizospheric microorganisms - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
A comparative study for the isolation of genomic DNA of rhizospheric microorganisms is described. The methods tested were based upon the methods of: (1) standard glass rod, (2) boiling glass rod, (3) Promega's Wizard genomic DNA isolation method, and (4) agarose gel plug, with some modifications of each method. The efficiency and suitability of the method for genomic DNA isolation were analysed based on three parameters : (1) the level of DNA purity, (2) the concentration of DNA, and (3) the intactness of the DNA. It was observed that the standard glass-rod method gave the best results in terms of DNA purity and the DNA concentration obtained. However, in terms of DNA intactness, agarose gel plug method gave the best result compared to other methods.